1964
DOI: 10.1111/j.1476-5381.1964.tb02033.x
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Parenteral Iron Haematinics in Nonpregnant, Pregnant and Lactating Rats

Abstract: The distribution of (59)Fe has been investigated in nonpregnant, pregnant and lactating rats and their young after injection of solutions containing a high molecular weight iron-dextrin complex (iron-dextrin, intravenously), and a low molecular weight complex of iron, sorbitol and citric acid (iron-sorbitol, intramuscularly), each labelled with (59)Fe. At different times after injection of a dose corresponding to 1.5 mg of iron per kg of body weight, the quantity of (59)Fe was determined in different organs, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1965
1965
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…He postulated that the complex was broken down in the RE-system giving a raised concentration of proteinbound plasma iron that passes through the placentae, probably resulting in an increased placental transfer of iron dependent on the foetal need. Hogberg & Lindvall (1964) drew the same conclusion for iron-dextrin in a comparative study between this complex and iron-sorbitol. In the case of iron-sorbitol an immediate transfer of iron to foetus was observed, but it was concluded that the transfer of the iron was an active process and not a simple diffusion of the complex.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…He postulated that the complex was broken down in the RE-system giving a raised concentration of proteinbound plasma iron that passes through the placentae, probably resulting in an increased placental transfer of iron dependent on the foetal need. Hogberg & Lindvall (1964) drew the same conclusion for iron-dextrin in a comparative study between this complex and iron-sorbitol. In the case of iron-sorbitol an immediate transfer of iron to foetus was observed, but it was concluded that the transfer of the iron was an active process and not a simple diffusion of the complex.…”
mentioning
confidence: 72%
“…The view that iron-dextran, iron-dextrin and iron-sorbitol do not pass the placental barrier has been based on studies of the iron moiety of the complexes (Sprent 1967, Nylander 1954, Hogberg & Lindvall 1964. In this study however, both the iron unit and the stabilizing carbohydrate unit in the iron-poly (sorbitol-gluconic acid) complex have been studied with regard to their transfer from the mother to the foetus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Wolf et al, 2020) Liquid preparations of iron causes staining of teeth. (Högberg and Lindvall, 1964) Figure 2: Forms of Drug Intake which explains about the various forms of haematinic intake. Among 100 respondents, 66% of patients where under taking tablets-(Folic acid,Iron,Vit B complex), where 20% were taking haematinics in form of syrups(iron), 2% of the patients were taking parenteral forms of iron and Vit B12 through injections.…”
Section: Resultsmentioning
confidence: 99%
“…Blood samples (1 ml) were also counted without pretreatment. Calculation of total radioactivity in blood was based on a blood volume of 4.75 ml per 100gbodyweight (Hogberg & Lindvall 1964). Correction for blood present in tissues was calculated according to Muelheims et a/.…”
Section: Analysis Of Urine and Bilementioning
confidence: 99%